Blood Levels of S-100 Calcium-Binding Protein B, High-Sensitivity C-Reactive Protein, and Interleukin-6 for Changes in Depressive Symptom Severity after Coronary Artery Bypass Grafting: Prospective Cohort Nested within a Randomized, Controlled Trial - Pearlman, Daniel M.; Brown, Jeremiah R.; MacKenzie, Todd A.; Hernandez, Felix; Najjar, Souhel (PloS one, 2014)
Cross-sectional and retrospective studies have associated major depressive disorder with glial activation and injury as well as blood-brain barrier disruption, but these associations have not been assessed prospectively. Here, we aimed to determine the relationship between changes in depressive symptom severity and in blood levels of S-100 calcium-binding protein B (S-100B), high-sensitivity C-reactive protein, and interleukin-6 following an inflammatory challenge. Fifty unselected participants were recruited from a randomized, controlled trial comparing coronary artery bypass grafting procedures performed with versus without cardiopulmonary bypass for the risk of neurocognitive decline. Depressive symptom severity was measured at baseline, discharge, and six-month follow-up using the Beck Depression Inventory II (BDI-II). The primary outcome of the present biomarker study was acute change in depressive symptom severity, defined as the intra-subject difference between baseline and discharge BDI-II scores. Blood biomarker levels were determined at baseline and 2 days postoperative. Changes in S-100B levels correlated positively with acute changes in depressive symptom severity (Spearman ρ, 0.62; P = 0.0004) and accounted for about one-fourth of their observed variance (R2, 0.23; P = 0.0105). This association remained statistically significant after adjusting for baseline S-100B levels, age, weight, body-mass index, or β-blocker use, but not baseline BDI-II scores (P = 0.064). There was no statistically significant association between the primary outcome and baseline S-100B levels, baseline high-sensitivity C-reactive protein or interleukin-6 levels, or changes in high-sensitivity C-reactive protein or interleukin-6 levels. Among most participants, levels of all three biomarkers were normal at baseline and markedly elevated at 2 days postoperative. Acute changes in depressive symptom severity were specifically associated with incremental changes in S-100B blood levels, largely independent of covariates associated with either. These findings support the hypothesis that glial activation and injury and blood-brain barrier disruption can be mechanistically linked to acute exacerbation of depressive symptoms in some individuals.